2017
DOI: 10.1111/tpj.13549
|View full text |Cite
|
Sign up to set email alerts
|

WRI1‐1, ABI5, NFYA3 and NFYC2 increase oil biosynthesis in coordination with hormonal signaling during fruit development in oil palm

Abstract: The oil biosynthesis pathway must be tightly controlled to maximize oil yield. Oil palm accumulates exceptionally high oil content in its mesocarp, suggesting the existence of a unique fruit-specific fatty acid metabolism transcriptional network. We report the complex fruit-specific network of transcription factors responsible for modulation of oil biosynthesis genes in oil palm mesocarp. Transcriptional activation of EgWRI1-1 encoding a key master regulator that activates expression of oil biosynthesis genes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 46 publications
2
45
0
Order By: Relevance
“…In addition to WRINKLED1, they identified two novel transcription factors, termed NF-YB-1 and ZFP-1, observed to activate fatty acid synthesis genes. The understanding of this transcription factor network in oil palm mesocarp was further extended by Yeap et al [96] in which EgWRI1-1 was found to be activated by three ABAresponsive transcription factors; EgNF-YA3, EgNF-YC2, and EgABI5. Two repressors of this network were also identified, EgWRKY40 and EgWRKY2, and overall this study enabled a hormone signaling network model to be postulated that coordinates fruit development and fatty acid biosynthesis.…”
Section: Oil Palm Omics Research Related To Yieldmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition to WRINKLED1, they identified two novel transcription factors, termed NF-YB-1 and ZFP-1, observed to activate fatty acid synthesis genes. The understanding of this transcription factor network in oil palm mesocarp was further extended by Yeap et al [96] in which EgWRI1-1 was found to be activated by three ABAresponsive transcription factors; EgNF-YA3, EgNF-YC2, and EgABI5. Two repressors of this network were also identified, EgWRKY40 and EgWRKY2, and overall this study enabled a hormone signaling network model to be postulated that coordinates fruit development and fatty acid biosynthesis.…”
Section: Oil Palm Omics Research Related To Yieldmentioning
confidence: 95%
“…Oleosins are not highly expressed in non-seed oil-accumulating tissues such as the mesocarp of olive, oil palm, and avocado [94]. Transcriptome studies on the oil-rich mesocarp of olive, oil palm, and avocado have also revealed important differences in the transcriptional control of lipid biosynthesis in the mesocarp to that of oil-rich seeds [49,90,91,[95][96][97]. In oil-rich seeds, many of the key regulators of embryogenic development and seed maturation, including abscisic acid-insensitive3 gene and LEAFY COTYLEDON group genes (e.g., LEC1, LEC1like, LEC2, and FUSCA3) control lipid biosynthesis through the downstream transcription factor WRINKLED1 [34,49,[98][99][100][101].…”
Section: Omics Studies Of Mesocarp Oil Cropsmentioning
confidence: 99%
“…In oil palm mesocarp, where most palm oil is derived from and EgWRI1 displays high expression, the inability to detect expression of key regulator genes, such as EgLEC1, EgLEC2, and EgFUS3, suggests that expression of EgWRI1 involves additional fruit-specific upstream regulators (Bourgis et al, 2011). EgNF-YA3, EgNF-YC2, and EgABI5 have been recently found to be capable of binding to the promoter region and activate the expression of EgWRI1 (Yeap et al, 2017).…”
Section: Regulators Controlling the Expression Of Wri1mentioning
confidence: 99%
“…Further studies showed that AtWRI1 also plays a role in processes such as lipid assembly, storage, flowering time, seed development, embryo maturation, plant hormone regulation, and photosynthesis (Cernac et al, 2006;Kong et al, 2017;Li et al, 2015;Maeo et al, 2009;Wu et al, 2014). A number of other communications have also revealed orthologs of AtWRI1 being involved in plant oil biosynthesis (Adhikari et al, 2016;Bhattacharya et al, 2016;Chen et al, 2017;Ivarson et al, 2016;Kang et al, 2017;Kim et al, 2016;Liu et al, 2010;Ma et al, 2013;Pouvreau et al, 2011;Shen et al, 2010;Vanhercke et al, 2013;Wu et al, 2014;Yeap et al, 2017). For example, expression of the Brassica napus WRI1(BnWRI1) in Arabidopsis promoted between 10% and 40% increased seed oil content and led to larger seed and size mass (Liu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%